KECERDASAN MAHASISWA SEBAGAI MEDIA INTERAKSI BELAJAR MENGAJAR - Ilmiyatur Rosidah (FKIP Universitas Islam Jember, 2016)
Intelligence is a god-gifted to everyone. Intellligence doesn’t mean that you are smart and expert in Science, Mathemathics or English. We have to build this paradigm to our students as the candidate of teachers because the intelligence cannot be measured by those kinds of achievement. To cultivate it, we have to give practical examples in teaching-learning processes by their own creativity and innovation which is in line with the intelligence of the teachers candidate.Keywords :students’ intelligence, media, teaching and learning interaction